Resistência mecânica do solo à penetração em áreas de mata nativa e cultivada com meloeiro - Dumas, Peter John (Universidade Federal Rural do Semi-Árido, 2019)
The physical characteristics of the soil are easily modified by the management of soil and agricultural crops. Thus, the present work had the objective of evaluating soil mechanical resistance to root penetration in native forest and when cultivated with melon. The collection was carried out in an area 100 X 100 m, and every 20 X 20 m of the plot. In the field the points were allocated and soil collections in a depth of 0-10; 10-20; 20-30; 30-40 cm. The following physical attributes were analyzed: particle size distribution (sand, silt, clay), gravimetric moisture, particle density, organic matter and soil mechanical resistance to penetration. The soil penetration resistance samples were collected in a non-regular 87-point mesh for the area under melon cultivation in a non-regular mesh of 8 points for the forest area. Next, a geostatistical technique was used for data interpolation and isovalues and semivariogram mapping for exponential variables. The averages obtained in the descriptive and spatial statistics for the cone index in the Cultivated Area and in the Mata Nativa Area were classified as medium to moderate. When evaluating the use of semivariogram, it was verified that in the studied variables there was a moderate and moderate spatial dependence, this characteristic allowed to estimate values for non-sampled sites, minimizing the errors associated to the estimate. In the two studied areas there was not enough density to impair root growth.
Monografia
Keywords: Manejo do solo; Semiárido; Conservação; Soil management; Semiarido; Conservation; CIENCIAS AGRARIAS::AGRONOMIA